2013
DOI: 10.21608/ajesa.2013.163737
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Seasonal abundance of Mites Associated with Two Varieties of Date Palm in Giza and Sohag Governorates, Egypt

Abstract: I 'q*".number of mites are known associated with different varieties of date palm throughout the world. Their distributional pattern is, however not constant eve4rwhere, which varies according to climatic factors. These mite species could be either Phytophagous, Parasitic, Predators, Phoresy in addition to" suproptugous and Fungivorous species' In this study 37 mite species representing 31 genera, 17 families, three Sub-ordeis, ictinedida; Gamasida and Acaridida were recorded. These mite species were c-lasiifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The official Egyptian biodiversity website stated that there is more than 15,000 insect species and more than 1,500 arachnid species of mites, ticks, scorpions and spiders as terrestrial fauna, and more than 1,800 invertebrate species in aquatic fauna (Available at: https://www.egyptheritage.com/BiodiversitySite/Biodiversity/index.html). Nevertheless, some studies have revealed arthropod biodiversity in different Egyptian agro-ecosystems (Abo- Shnaf et al, 2008;Sallam et al, 2010;Sawaby, et al, 2010;El-Sanady and Mohamed, 2013;Imam and Sawaby, 2013 a & b;Zaki et al, 2015;Abd El-Karim, et al, 2016;Abo-Shnaf et al, 2016;Rizk, et al, 2017;Zaki and Aly, 2018;2019;Zaki and Abo-Shnaf, 2018;El-Sheikh, et al, 2020;Zaki, 2021). Also, genera of phylum Nematoda, Meloidogyne Göldi, 1889 was the most dominant genus, and Xiphinema Cobb, 1913 was the rarest genus recorded in SEKEM (Adam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The official Egyptian biodiversity website stated that there is more than 15,000 insect species and more than 1,500 arachnid species of mites, ticks, scorpions and spiders as terrestrial fauna, and more than 1,800 invertebrate species in aquatic fauna (Available at: https://www.egyptheritage.com/BiodiversitySite/Biodiversity/index.html). Nevertheless, some studies have revealed arthropod biodiversity in different Egyptian agro-ecosystems (Abo- Shnaf et al, 2008;Sallam et al, 2010;Sawaby, et al, 2010;El-Sanady and Mohamed, 2013;Imam and Sawaby, 2013 a & b;Zaki et al, 2015;Abd El-Karim, et al, 2016;Abo-Shnaf et al, 2016;Rizk, et al, 2017;Zaki and Aly, 2018;2019;Zaki and Abo-Shnaf, 2018;El-Sheikh, et al, 2020;Zaki, 2021). Also, genera of phylum Nematoda, Meloidogyne Göldi, 1889 was the most dominant genus, and Xiphinema Cobb, 1913 was the rarest genus recorded in SEKEM (Adam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%